Fenomena Dan Terminasi Diapause Penggerek Batang Padi Putih (Scirpophaga Innotata) = Diapause Phenomenon And Termination Of The White Rice Stemborer - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana Universitas Gadjah Mada, 1999)
Diapause of larvae of the white Stem borers, Scirpophaga innotata (Walker), is interesting and can be terminated by exposing them in a certain low thennoperiod, so that *he brain is activated to initiate the production of prothoracotropic hormone (PTTH)_ In this ase water is strongly suggested responsible for stabilizing this low thermoperiml by izechanism of buffering (capture and release) heat.